2023
DOI: 10.1038/s41598-023-28030-3
|View full text |Cite
|
Sign up to set email alerts
|

Report on the first detection of Asian citrus psyllid Diaphorina citri Kuwayama (Hemiptera: Liviidae) in the Republic of Benin, West Africa

Abstract: The Asian citrus psyllid (ACP), Diaphorina citri, was detected for the first time in the Republic of Benin, West Africa. The ACP is a known vector of Candidatus Liberibacter asiaticus (CLas), the putative causal agent of the devastating Huanglongbing (HLB; citrus greening disease). During visual surveys, ACP was only observed on residential citrus trees in southern Benin, but not in residential areas or commercial groves in the central and northern parts of the country. Its identity was confirmed morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The role of rainfall on the increase and decrease of ACP population was also significant. Sétamou et al (2023) reported that heavy rainfall is linked with low population of psyllid, as this amount of rainfall washes out eggs and nymphs of psyllid, while low rainfall favours psyllid population (Devi and Sharma, 2014). The seasonal distribution of psyllid completely depends on the rainfall (Devi and Sharma, 2014).…”
Section: Effect Of Environmental Variables On Acp Population During Y...mentioning
confidence: 99%
“…The role of rainfall on the increase and decrease of ACP population was also significant. Sétamou et al (2023) reported that heavy rainfall is linked with low population of psyllid, as this amount of rainfall washes out eggs and nymphs of psyllid, while low rainfall favours psyllid population (Devi and Sharma, 2014). The seasonal distribution of psyllid completely depends on the rainfall (Devi and Sharma, 2014).…”
Section: Effect Of Environmental Variables On Acp Population During Y...mentioning
confidence: 99%
“…Digital image analyses for plant disease diagnosis are increasingly being used. Convolutional neural networks (CNNs) incorporating image analyses of individual plant leaves have been examined as classification models, particularly under a controlled laboratory environment [ 4 ]. For instance, deep learning techniques with machine learning are used in citrus disease diagnosis systems [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…C ITRUS production and quality face significant threats from diseases, such as citrus canker, insect pests, water availability, and climate change (Syed-Ab-Rahman et al, 2022; Shafqat et al, 2021). Among these issues, citrus diseases have emerged as a primary factor contributing to reduced yield, compromised fruit quality, and shortened tree lifespan worldwide (Sétamou et al, 2023). As a result, citrus exports to key global markets, including the European Union (EU) and American citrus markets, are hindered due to quarantine measures aimed at controlling fruit diseases like citrus canker .…”
Section: Introductionmentioning
confidence: 99%